Cluster Analysis for Corpus Linguistics - Moisl, Hermann (De Gruyter, 2015)
The series Quantitative Linguistics publishes books on all aspects of quantitative methods and models in linguistics, text analysis and related research fields. Specifically, the scope of the series covers the whole spectrum of theoretical and empirical research, ultimately striving for an exact mathematical formulation and empirical testing of hypotheses: observation and description of linguistic data, application of methods and models, discussion of methodological and epistemological issues, modelling of language and text phenomena.
Description based on publisher supplied metadata and other sources
Keywords: Cluster-Analyse; Korpus